PARENTS’ DETERMINANT FACTORS OF CHOOSING BETWEEN PRIVATE AND PUBLIC SCHOOL (MA) FOR THEIR CHILDREN - Rizky Dwi Ratna Septinawati; Fadly Usman (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
In the context of education, parents' decision to choose a school for their children is a crucial aspect that affects their children's educational experience and outcomes. This study investigates the factors that influence parents' decision in choosing between private and public schools for their children's senior secondary education (MA). A quantitative method was adopted by distributing questionnaires through Google Form to parents of MA students. The main objective of this study is to identify the important variables that influence this choice and to understand how these factors interact in the decision-making process. The questionnaire was designed to measure aspects such as perceptions of the quality of education, cost, facilities, location, school reputation, and compatibility with family values. Data analysis was conducted using statistical techniques to evaluate the relationship between these factors and school selection decisions. The study sample included responses from hundreds of parents, providing a broad representation of the perspectives of various socioeconomic groups. The results show that factors such as the quality of education, cost, and the compatibility of school values with family values are major considerations in this decision. In particular, private schools are often chosen due to the perception of higher quality of education, while public schools are preferred due to cost and location accessibility. The study also found that religious and moral values play an important role, especially for families who prioritize Islamic education in school selection. The conclusions of this study provide valuable insights for school managers and education policy makers to optimize their strategies in attracting and meeting parents' needs. The study also makes a significant contribution to the literature on education management and school choice.